Dog Care Center in Badung, Bali Application of Harmony Concept in Space Design in Dog Custody - Putra, I Gede Aldy Susanto Eka; Agusintadewi, Ni Ketut; Suryada, I Gusti A gung Bagus (Journal of A Sustainable Global South, 2018)
Dogs are animals that have high popularity as pets in the global community. Indonesia is no exception, but people still do not understand the responsibility for caring dogs as pets. This has an impact on the dog's assumption only as a comforter without thinking about the importance of their needs and care. Because there is a considerable comparison between the level of dog popularity and the sense of responsibility for caring dogs as pets, a place is needed to harmonize the gap. The Dog Care Center is needed to educate the public and provide facilities for dog needs and care, with the theme of Natural Living design that takes the concept of Harmony in the design of the interior. The choice of harmony concept has an emphasis on the design of space, material and color that can give the impression of openness without the separation between human and dog in it. Index Terms — dog, care, center, harmony.